Cultivating a scholarly community of practice - Lotz-Sisitka, Heila; Ellery, Karen; Olvitt, Lausanne; Schudel, Ingrid; O’Donoghue, Rob (Acta Academica: Critical views on society, culture and politics, 2010)
In the field of Environment and Sustainability Education we are seeking ways of developing our teaching and supervision practices to enable social changes in a rapidly transforming field of practice where global issues of truth, judgement, justice and sustainability define our engagements with the public good. This article explores the process of cultivating a scholarly community of practice as a model of supervision that not only engages scholars in an intellectual community oriented towards socio-ecological transformation, but also extends and enhances dialogue with individuals on the technical and theoretical aspects of their postgraduate studies.